An Overview of the Utilization of PET Plastic Bottle Waste for Membrane Fabrication - Istirokhatun, Titik; Siahaan, Samuel Ezra; Gonzales, Ralph Rolly; Andarani, Pertiwi; Susanto, Heru; Filardli, Abdullah Malik Islam (Universitas Diponegoro, 2025)
Plastic use, in this case including plastic drinking water bottles particularly polyethylene terephthalate (PET) has resulted in significant environmental, social, economic, and health repercussions. It will ultimately be deposited in landfills, requiring up to 1,000 years for each individual bottle to degrade. This review begins by briefly introducing the composition and characteristics of PET. It then details the methods for converting waste PET into valuable materials for diverse applications. The review emphasizes advanced uses of these materials in water treatment, highlighting the development of robust, organic solvent-resistant membranes. The primary aim of this review is to evaluate recent studies of PET bottle recycling to membrane technologies, membrane fabrication from PET waste, applications of PET-based membranes, advantages and challenges of using PET waste for membrane fabrication.